Compulsory military service and personality development - Johannes Schult; Jörn R. Sparfeldt (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
Compulsory military service is a uniformed life event disrupting the lives of young men (and sometimes women) in countries with conscription. Consequently, the development of personality and subjective well-being during service was investigated using representative population data from the German Socio-Economic Panel. In line with previous findings, men who chose military service revealed descriptively lower agreeableness than those who did civil service (d = -0.33). Contrasting previous research, agreeableness ratings remained stable in both groups. Conscientiousness increased in both groups (n2 = .067). The potentially disruptive nature of conscription is not reflected in the present longitudinal results.Overall, personality traits and life satisfaction appear to remain remarkably stable despite the substantial changes of living environments and daily routines associated with military service.
Keywords: 330; personality development; Big Five; subjective well-being; life event; draft; military conscription